Simple synthesis of new mixed isocyanide-NHC-platinum(ii) complexes and their catalytic activity - Hubbert, Christoph; Breunig, Marcus; Carroll, Kristen J.; Rominger, Frank; Hashmi, A. Stephen K. (Australian journal of chemistry, 2014)
Using the new modular and convergent approach to isocyanide-N-hetrocyclic carbene-platinum(ii) complexes, eight new compounds have been synthesised. For three of these, detailed structural data could be obtained by X-ray crystal structure analyses. This new family of organoplatinum complexes is catalytically active for hydrosilylation reactions; styrene and phenylacetylene could be used as substrates; triethylsilane and 1,1,1,3,5,5,5-heptamethyltrisiloxane could be used as reagents. With some of the new platinum pre-catalysts, excellent regioselectivities of up to 98 : 2 could be obtained, and turnover numbers up to 840 were achieved.